Evaluation Of The Performance Of Fatty Acid Methyl Ester (Fame) As An Alternative Solvent In Alkyd Resin-Based Paints - Arya Wiranata; Bahruddin Bahruddin; Zuchra Helwani; Heni Sugesti; Yogi Chandra; Hasrul Hasrul; Trisuciati Syahwardini; Ni putu Vidya Primarista (LAVOISIER: Chemistry Education Journal, 2026)
The use of conventional solvents in the oil paint industry often leads to volatile organic compound (VOC) emissions and toxicity, so this study aims to evaluate the potential of Fatty Acid Methyl Ester (FAME) as an environmentally friendly alternative solvent. FAME is synthesised from vegetable oil through a transesterification reaction, then formulated into alkyd resin-based paints with varying binder content (40%, 50%, and 60%) to be compared with acetone solvent. The paint performance evaluation includes tests on drying time, gloss level, hiding power, and Whiteness and Yellowness Index. The results show that FAME-based paints have a much higher gloss level (10–26 GU) than acetone (3–6 GU) because their slower evaporation rate provides optimal levelling time, though this results in much longer drying time, namely 780–819 minutes. In addition, FAME has been proven to produce better covering power and a lower Yellowness Index (1.39–4.15) than acetone (4.09–5.74). This superiority is influenced by the nature of FAME, which minimises damage to the polymer binder and uniformly disperses pigments, preventing agglomeration. Overall, FAME has great potential as a sustainable paint solvent that can improve optical and physical properties, although its formulation still requires optimisation to accelerate drying.